1983
DOI: 10.1159/000115563
|View full text |Cite
|
Sign up to set email alerts
|

Sensorimotor Neuropathy in a Patient with Marinesco-Sjögren Syndrome

Abstract: A case of Marinesco-Sjögren syndrome, displaying the characteristic signs (ataxia, congenital cataract and mental retardation) is presented. Electrophysiological examination pointed to the presence of a sensorimotor peripheral neuropathy with an underlying mixed process of segmental demyelination and axonal degeneration (probably secondary). The sural nerve and gastrocnemius biopsy confirmed these data, showing that in this case the segmental demyelination process was accompanied by axonal degeneration.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

1988
1988
2005
2005

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…However, several patients with MSS have had elevated CK levels and myopathic features on muscle biopsy [Komiyama et al, 1989; McLaughlin et al, 1996]. Neurogenic muscular atrophy [Zimmer et al, 1992], demyelinating polyneuropathy [Zimmer et al, 1992; Müller‐Felber et al, 1998], and sensorimotor peripheral neuropathy with segmental demyelination [Alexianu et al, 1983] have also been observed. Muscle biopsies have revealed increased variation of fiber size with fiber‐type disproportion and scattered atrophic fibers, vacuolar degeneration of the muscle fibers, necrosis, and increased adipose tissue [Zimmer et al, 1992; Ishikawa et al, 1993; McLaughlin et al, 1995; Müller‐Felber et al, 1998].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, several patients with MSS have had elevated CK levels and myopathic features on muscle biopsy [Komiyama et al, 1989; McLaughlin et al, 1996]. Neurogenic muscular atrophy [Zimmer et al, 1992], demyelinating polyneuropathy [Zimmer et al, 1992; Müller‐Felber et al, 1998], and sensorimotor peripheral neuropathy with segmental demyelination [Alexianu et al, 1983] have also been observed. Muscle biopsies have revealed increased variation of fiber size with fiber‐type disproportion and scattered atrophic fibers, vacuolar degeneration of the muscle fibers, necrosis, and increased adipose tissue [Zimmer et al, 1992; Ishikawa et al, 1993; McLaughlin et al, 1995; Müller‐Felber et al, 1998].…”
Section: Discussionmentioning
confidence: 99%
“…We recorded the ophthalmological, neurological, and orthopedic manifestations together with developmental history, craniofacial dysmorphism, digital anomalies, and MRI scan findings. The cases reviewed were the following: Alter et al [1962] (4 cases); Skre and Berg [1977] (11 cases); Hakamada et al [1981] (1 case); Alexianu et al [1983] (1 case); Walker et al [1985] (4 cases); Herva et al [1987] (4 cases); Superneau et al [1987] (6 cases); Sewry et al [1988] (3 cases); Komiyama et al [1989] (4 cases); Bromberg et al [1990] (2 cases); Katafuchi et al [1990] (1 case); Tachi et al [1991] (1 case); Torbergsen et al [1991] (7 cases); Kodama et al [1992] (2 cases); Zimmer et al [1992] (6 cases); Ishikawa et al [1993] (1 case); Brogdon et al [1996] (9 cases); McLaughlin et al [1996] (3 cases); Williams et al [1996] (1 case); Farah et al [1997] (2 cases); Müller‐Felber et al [1998] (4 cases); Aguglia et al [2000] (2 cases); Reinker et al [2002] (2 cases). The case reports of Brogdon et al [1996] and Superneau et al [1987] appear to describe the same family, and the total number of patients counted from both reports was 9 rather than 15.…”
Section: Methodsmentioning
confidence: 99%
“…Skre et al also reported such a case with loss of anterior horn motoneurons (22). Another case with sensory peripheral neuropathy in a sural nerve with segmental demyelination and neurogenie atrophy of the quadriceps muscle was described by Alexianu et al (1). The data suggest that there are two variants of the syndrome, one with a myopathic and the other with a neurogenic type of lesion.…”
Section: Discussionmentioning
confidence: 93%
“…Cataracts can be congenital 7,12,[17][18][20][21] or may develop at a later age with a variable rate of progression. Cataracts can be congenital 7,12,[17][18][20][21] or may develop at a later age with a variable rate of progression.…”
Section: Discussionmentioning
confidence: 99%